Hematological parameters as predictors of complex angiographic coronary lesions in patients with acute myocardial infarction - Thadzia Maria de Brito Ramos; José Gildo de Moura Monteiro Júnior; Veridiana Câmara Furtado; Maria Luísa Souza de Paula; Bárbara Farias Bastos; Maria Júlia Ordônio Pires; Ulisses Ramos Montarroyos; Dário Celestino Sobral Filho (PLoS ONE, 2026)
Acute myocardial infarction is an essentially inflammatory disease. The inflammation is predictive of adverse clinical outcomes in coronary artery disease, and the Syntax Score was developed as an angiographic scoring system to anatomically classify the complexity of atherosclerosis plaques. The inflammatory response leads to an increase in mean platelet volume (MPV), neutrophil/lymphocyte ratio (NLR) and the appearance of nucleated red blood cells (NRBCs) in the peripheral blood of the patients with acute myocardial infarction. These hematological variables express systemic inflammation and hypoxia; therefore, they are markers of these tissue injuries. Severe abnormalities in these parameters are associated with a worse prognosis and were organized within a hematologic scoring system, i.e., a hematologic score. The objective of this study was to determine the sensitivity and specificity of these hematologic biomarkers in order to estimate the angiographic severity of coronary lesions. This was a secondary analysis of a larger study “Laboratory Model for Stratification of Risk of Intra-hospital Death Associating Hematological Score, Immunological Markers and Metalloproteinases in Patients with Acute Myocardial Infarction”, conducted by our research group. Individuals hospitalized with a diagnosis of acute myocardial infarction and undergoing coronary angiography during hospitalization were included in the study. Upon admission to the health service, nucleated red blood cell count, neutrophil/lymphocyte ratio, and mean platelet volume were obtained. Pregnant women, patients with oncological or hematological diseases, those with prior use of corticosteroids or chemotherapy, and those who returned to the hospital after discharge were excluded. A total of 479 patients, aged 62.3 ± 11.1 years, were studied, 63% of whom were male. In this study, the significant presence of NLR or MPV, with values ≥ 10.4 and ≥ 3.7, respectively, correlated well with a high syntax score (sensitivity 81.8%, specificity 15.9%, negative predictive value 92.2%).